Bifunctional CuNi/CoOx catalyst for mild-temperature in situ hydrodeoxygenation of fatty acids to alkanes using isopropanol as hydrogen source. (1st April 2020) - Wang, Juncheng; Xu, Ling; Nie, Renfeng; Lyu, Xilei; Lu, Xiuyang
Graphical abstract: Highlights: Cum Nin /CoOx was used for oleic acid hydrodeoxygenation with isopropanol. 100% conversion and 91.3% heptadecane yield were obtained at 240 °C for 8 h. Strong synergy between Cu, Ni and CoOx favored H2 production ability. The rate determining step relied on octadecanol dehydrogenation. Oleic acid hydrodeoxygenation occurred via decarbonylation of stearaldehyde. Abstract: Bifunctional Cum Nin /CoOx catalysts were fabricated by co-precipitation method and applied in in-situ hydrodeoxygenation (HDO) of biomass derived oleic acid to n-heptadecane with isopropanol as hydrogen source. Upon incorporating Cu or Ni into CoOx, the catalytic performance could be easily boosted. By varying Cu/Ni ratio, reduction temperature as well as catalyst loading, the optimized Cu1 Ni1 /CoOx exhibited >99% conversion and 91.3% n-heptadecane yield at 240 °C in 8 h. Characterizations showed that synergistic effect between Cu, Ni and CoOx was existed, thus strengthening H2 production ability towards isopropanol and favoring the generation of n-heptadecane. Kinetic studies revealed HDO of oleic acid to alkane mainly proceeded via decarbonylation of stearaldehyde rather than direct decarboxylation of stearic acid, and the rate determining step relied on octadecanol dehydrogenation. This catalyst could be magnetically separated for 5 times recycling and was versatile for in situ HDO of various fatty acids, thus achieving a low-cost, energy-saving biomass-to-biofuel conversion.